Sofia's Dream - Land Wilson (CA, United States Little Pickle Press LLC, 2015)
In this magically illustrated and delightfully rhyming bedtime story, little Sofia befriends the Moon and sets off on a dreamy adventure to visit her friend. She sees our planet from the Moon's point of view and is inspired to do whatever she can to protect our Earth. When she wakes, Sofia encourages others to do the same. "Once you see from this distant view, Awareness may come over you. By far your gift of greatest worth Is our dear home, this planet Earth." Sofia's Dream was inspired by the author's interviews with three Apollo astronauts, about how viewing Earth from space affected their sense of responsibility for the health of our planet.
Keywords: Circle Time + Earth Day + Environment